Experimentally mapping the oriented-to-misoriented transition in laser powder bed fusion Ti-10%Mo alloys. (1st July 2023) - Peterson, Jack; Kariya, Shota; Issariyapat, Ammarueda; Umeda, Junko; Kondoh, Katsuyoshi
Abstract: Understanding the oriented-to-misoriented transition (OMT) and its origins is critical to additive manufacturing design processes. The Ti – 10 wt.% Mo alloy was printed at laser scan speeds ranging from 500 mm/s to 2500 mm/s and volumetric energy densities (VED) ranging from 50 J/mm 3 to 150 J/mm 3 . A technique for rapidly mapping the OMT over the design space using X-ray diffraction was developed with electron backscattered diffraction verification. Mapping of the OMT revealed two independent transitions as functions of scan speed and VED respectively. Cross sections of in-situ single track scans at constant VED revealed the scan speed based OMT to be caused by a decrease in penetration depth and larger equiaxed grain zones during weld pool solidification. Graphical abstract: Image, graphical abstract